2018
DOI: 10.1111/mcn.12640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipid‐based nutrient supplements or multiple micronutrient supplements compared with iron and folic acid supplements during pregnancy on maternal haemoglobin and iron status

Abstract: We examined the effect of three types of prenatal supplements containing different amounts of iron on haemoglobin (Hb) and iron status (zinc protoporphyrin [ZPP] and soluble transferrin receptor [sTfR]) in late pregnancy among 1,379 women in rural Malawi. Participants were recruited at ≤20 gestational weeks (gw) and randomly assigned to consume daily (1) 60‐mg iron and folic acid (IFA); (2) 20‐mg iron plus 17 micronutrients in a capsule (MMN); or (3) lipid‐based nutrient supplement (LNS; 118 kcal) with 20‐mg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Women from these trials were included in this cohort study if they had: 1 ) at least one measurement of Hb concentration or iron status, at either enrollment or 36 weeks of gestation, and 2 ) any newborn anthropometric measurement or an estimated pregnancy duration. We have previously reported that supplementation with SQ-LNSs or multiple micronutrients resulted in lower Hb and iron status at 36 weeks of gestation than for the iron and folic acid trial arm (22, 23). Assigned supplement group in the main trial was not the focus of the current study and was controlled for in analyses of the 36-wk measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Women from these trials were included in this cohort study if they had: 1 ) at least one measurement of Hb concentration or iron status, at either enrollment or 36 weeks of gestation, and 2 ) any newborn anthropometric measurement or an estimated pregnancy duration. We have previously reported that supplementation with SQ-LNSs or multiple micronutrients resulted in lower Hb and iron status at 36 weeks of gestation than for the iron and folic acid trial arm (22, 23). Assigned supplement group in the main trial was not the focus of the current study and was controlled for in analyses of the 36-wk measurements.…”
Section: Methodsmentioning
confidence: 99%
“…We screened 19 studies, after which a total of 11 trials were included and contributed to the analyses of the three outcomes of interest. One trial 32 was excluded because of the intermittent (twice weekly) supplementation scheme, four trials 33 , 34 , 35 , 36 were excluded because hemoglobin was not assessed in the third trimester, two trials 15 , 16 , 17 , 18 were excluded because MMS provided 20 mg of iron, and one trial 37 was excluded because of lack of relevant information, for example, the amount of iron provided in both groups was not available.…”
Section: Resultsmentioning
confidence: 99%
“…Exclusion criteria for this analysis were: (1) trials that did not assess third trimester iron‐related outcomes (e.g., assessed only postpartum); (2) trials with nondaily supplementation regimens; (3) trials conducted in high‐income countries (e.g., Brough); 14 and (4) trials that provided MMS with 20 mg of iron (Ashorn 15 , 16 and Dewey 17 , 18 ), because this dose is not relevant for our comparison of interest, which is the difference between 60 mg of iron as used in many IFA supplementation programs and 30 mg dose of iron in MMS.…”
Section: Methodsmentioning
confidence: 99%
“…Antenatal iron use is associated with reduced risk of maternal anaemia [39]. Receiving LNS (with 20 mg iron) in the iLiNS-DYAD-Malawi trial was associated with a higher risk of maternal anaemia at 36 gestation weeks, compared to IFA with 60 mg of iron [40]. This therefore indicates that LNS could not have prevented FGR by reducing the risk of maternal anaemia in this study.…”
Section: Discussionmentioning
confidence: 95%